Coordination of Village Security Institutions in Improving Conditions in Sidoarjo Regency - Silvi Nur Kristianingsih; Isnaini Rodiyah (Indonesian Journal of Cultural and Community Development, 2022)
Security and community expectations are basic needs that are always carried out in daily activities. Village security is a policy that ensures security and public relations to achieve national development goals, one of which is ensuring security and upholding the law. The method used is descriptive qualitative data obtained through observation, documentation, interviews and the use of sources from books, journals, and policy documents. The results of this study indicate that the coordination of the security institutions in Ketimang Village, especially on the awareness of good coordination with the existence of ego-sectoral relations between one another, causes disharmony in the relationship between village security institutions.